2018
DOI: 10.1096/fj.201801991r
|View full text |Cite
|
Sign up to set email alerts
|

The Streptococcus agalactiae complement interfering protein combines multiple complement‐inhibitory mechanisms by interacting with both C4 and C3 ligands

Abstract: Group B Streptococcus (GBS) colonizes the human lower intestinal and genital tracts and constitutes a major threat to neonates from pregnant carrier mothers and to adults with underlying morbidity. The pathogen expresses cell-surface virulence factors that enable cell adhesion and penetration and that counteract innate and adaptive immune responses. Among these, the complement interfering protein (CIP) was recently described for its capacity to interact with the human C4b ligand and to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Complement interfering protein (CIP) expressed on the surface of group B. Streptococcus (GBS) enables cell adhesion and penetration and impedes innate and adaptive immune responses. It was found that CIP was able to interact with the human C4b ligand and to interfere with the classical-and lectincomplement pathways (83). Clinical Staphylococcus aureus (S. aureus) strains can recruit complement regulator C4-binding protein (C4BP) to S. aureus surface to inhibit C4 complement effectors through binding significant amounts of the C4BP from serum.…”
Section: Complement C4 In Microbial Infectionmentioning
confidence: 99%
“…Complement interfering protein (CIP) expressed on the surface of group B. Streptococcus (GBS) enables cell adhesion and penetration and impedes innate and adaptive immune responses. It was found that CIP was able to interact with the human C4b ligand and to interfere with the classical-and lectincomplement pathways (83). Clinical Staphylococcus aureus (S. aureus) strains can recruit complement regulator C4-binding protein (C4BP) to S. aureus surface to inhibit C4 complement effectors through binding significant amounts of the C4BP from serum.…”
Section: Complement C4 In Microbial Infectionmentioning
confidence: 99%
“…Streptococcal toxic shock syndrome is the most serious of these diseases and requires prompt treatment. Since S. agalactiae is also a capsular-bearing bacterium, we hypothesized that the mechanism of streptococcal toxic shock syndrome might involve inhibition of the C5 protein induced by eculizumab (16), although no streptococcal infections have been reported in phase III trials or post-market surveillance in Japan (13). Eculizumab inhibits membrane attack complex formation and may accelerate the growth of S. agalactiae.…”
Section: Discussionmentioning
confidence: 99%
“…Complement and anti-GBS polysaccharide capsular antibodies are felt to be essential in host defense against invasive GBS disease, and both processes may be impaired in patients with ALL. [16][17][18] Determining the appropriate initial anti-neoplastic therapy posed a significant challenge in this case. Infection is a major cause of treatment-related mortality in pediatric ALL.…”
Section: Discussionmentioning
confidence: 99%